Gender and plantation labour in Africa : the story of tea pluckers' struggles in Cameroon - Konings, Piet (Langaa Research and Publishing CIG ; African Studies Centre, 2012)
This book explores the relationship between plantation labour and gender in Africa. Such a study is the more opportune because most of the existing works on plantation labour in Africa seem to have either under-studied or even ignored the changing conceptions of gender on the continent in recent times. One of the book's major concerns is to demonstrate that the introduction of plantation labour during colonial rule in Africa has had significant consequences for gender roles and relations within and beyond the capitalist labour process. The book focuses on two tea estates in Anglophone Cameroon.